2001
DOI: 10.1152/jappl.2001.91.3.1341
|View full text |Cite
|
Sign up to set email alerts
|

Normalized force, activation, and coactivation in the arm muscles of young and old men

Abstract: The purpose of this study was to determine whether the loss of muscle strength in the elderly could be explained entirely by a decline in the physiological cross-sectional area (PCSA) of muscle. Isometric force, muscle activation (twitch interpolation), and coactivation (surface electromyograph) were measured during maximal voluntary contractions (MVCs) of the elbow flexors (EFs) and extensors (EEs) in 20 young (23 +/- 3 yr) and 13 older (81 +/- 6 yr) healthy men. PCSA was determined using magnetic resonance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
236
9
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(278 citation statements)
references
References 50 publications
25
236
9
7
Order By: Relevance
“…The findings of increased CSA at the part of elbow flexors with largest CSA in L+A could be due to the acute elevation of anabolic hormones during the strength training. Furthermore, it has been observed that the largest CSA of a muscle determines the maximum strength of the muscle (Bamman et al 2000;Klein et al 2001), and consequently the increase in CSA in the L+A arm is the likely mechanism behind the superior 1RM improvement in L+A. The findings of increased CSA and strength after strength training without any acute elevations in circulatory hormones are in agreement with the findings of Wilkinson et al (2006).…”
Section: Discussionsupporting
confidence: 76%
“…The findings of increased CSA at the part of elbow flexors with largest CSA in L+A could be due to the acute elevation of anabolic hormones during the strength training. Furthermore, it has been observed that the largest CSA of a muscle determines the maximum strength of the muscle (Bamman et al 2000;Klein et al 2001), and consequently the increase in CSA in the L+A arm is the likely mechanism behind the superior 1RM improvement in L+A. The findings of increased CSA and strength after strength training without any acute elevations in circulatory hormones are in agreement with the findings of Wilkinson et al (2006).…”
Section: Discussionsupporting
confidence: 76%
“…They also reported a similar increase in M. Triceps Brachii co-activation during elbow flexion in their elderly participants (Klein et al, 2001). Contrary to their findings, in our study the coactivation of the M. Triceps Brachii during elbow flexion was equal in both groups and comparable to the co-activation level of the M Biceps Brachii during elbow extension in the young subjects.…”
Section: Accepted M Manuscriptmentioning
confidence: 64%
“…In the elderly subjects we observed a significantly higher M. Biceps Brachii co-activation during maximal isometric extension of the elbow compared to the young ones (8±3% higher, p<0.01). Also Klein et al reported a +/-5% higher M. Biceps Brachii co-activation in elderly compared to young subjects during maximal isometric elbow extension (Klein et al, 2001). …”
Section: Accepted M Manuscriptmentioning
confidence: 96%
See 1 more Smart Citation
“…It is well known that normal aging influences cognitive functions [2,13,24,40,41] and sensorimotor control of actions [22,43,44]. The state of musculoskeletal system, in particular that of muscular mechanics and structure, is also modified [17,23,26,32,46,47,49]. At the neural level, clear differences emerge when comparing brain's activation between elderly and young people during the performance of motor or cognitive tasks.…”
Section: Introductionmentioning
confidence: 99%